Human immunodeficiency virus infection does not worsen prognosis of liver transplantation for hepatocellular carcinoma. Issue 2 (4th January 2016) - Agüero, Fernando; Forner, Alejandro; Manzardo, Christian; Valdivieso, Andres; Blanes, Marino; Barcena, Rafael; Rafecas, Antoni; Castells, Lluis; Abradelo, Manuel; Torre‐Cisneros, Julian; Gonzalez‐Dieguez, Luisa; Salcedo, Magdalena; et al.
Abstract : The impact of human immunodeficiency virus (HIV) infection on patients undergoing liver transplantation (LT) for hepatocellular carcinoma (HCC) is uncertain. This study aimed to assess the outcome of a prospective Spanish nationwide cohort of HIV‐infected patients undergoing LT for HCC (2002‐2014). These patients were matched (age, gender, year of LT, center, and hepatitis C virus (HCV) or hepatitis B virus infection) with non‐HIV‐infected controls (1:3 ratio). Patients with incidental HCC were excluded. Seventy‐four HIV‐infected patients and 222 non‐HIV‐infected patients were included. All patients had cirrhosis, mostly due to HCV infection (92%). HIV‐infected patients were younger (47 versus 51 years) and had undetectable HCV RNA at LT (19% versus 9%) more frequently than non‐HIV‐infected patients. No significant differences were detected between HIV‐infected and non‐HIV‐infected recipients in the radiological characteristics of HCC at enlisting or in the histopathological findings for HCC in the explanted liver. Survival at 1, 3, and 5 years for HIV‐infected versus non‐HIV‐infected patients was 88% versus 90%, 78% versus 78%, and 67% versus 73% ( P = 0.779), respectively. HCV infection (hazard ratio = 7.90, 95% confidence interval 1.07‐56.82) and maximum nodule diameter >3 cm in the explanted liver (hazard ratio = 1.72, 95% confidence interval 1.02‐2.89) were independently associated with mortality in the whole series. HCC recurred in 12 HIV‐infected patients (16%) and 32 non‐HIV‐infected patients (14%), with a probability of 4% versus 5% at 1 year, 18% versus 12% at 3 years, and 20% versus 19% at 5 years ( P = 0.904). Microscopic vascular invasion (hazard ratio = 3.40, 95% confidence interval 1.34‐8.64) was the only factor independently associated with HCC recurrence. Conclusions : HIV infection had no impact on recurrence of HCC or survival after LT. Our results support the indication of LT in HIV‐infected patients with HCC. (Hepatology 2016;63:488–498)